Lectin Activity in Gut Extract of Culex pipiens. - Mona Koosha; Mohammad Reza Abai; Mandan Abolhasani; Soroor Charedar; Hamid Reza Basseri (Journal of Arthropod-Borne Diseases, 2013)
Background: The role of lectins is important in interaction between pathogens and mosquito vectors. This study was performed to identify agglutinin activities of protein molecules on the midgut of Culex pipiens. Methods: Culex pipiens was reared in insectray condition and the midguts of males and females (blood fed and un- fed) were dissected separately in Tris-HCl buffer. The extracts of midguts were applied for hemagglutinin assay against red blood cells of rabbit, mouse, rat, dog, horse, sheep, guinea pig, cow, human (A, B, AB, O groups). Then, the RBCs with relatively high agglutinin activity were chosen for carbohydrate inhibition assay. D (+) glucose, D (+) galactose, D (+) mannose, D (-) fructose, D (-) arabinose, L (-) fucose, lactose, N-acetyl-D-glucosamine, N-acetyl-Dgalactosamine, sialic acid were used to specify carbohydrate binding lectin. Results: The highest agglutinin activities were found against sheep and rabbits RBCs. Sexual diversity of agglutinin activities was observed among midgut extraction of males and females. In addition, variation in agglutinin activity of blood fed and unfed female mosquitoes were detected. The lectin activity was inhibited highly with glucose, galactose, fucose and fructose but less inhibitor activities was observed by arabinose, N-acetyl-D-galactosamine, n- acetyl-d-glucosamine, lactose and mannose. Conclusion: The secretion of hemagglutinins (lectins or lectin-like molecules) in the digestive system depends on the type of food in the gut. This suggests that emptying of the gut in preparation for protein rich food probably starts the secretion of hemagglutinins.